Ultrafast low-temperature near-seamless joining of Cf/SiC using a sacrificial Pr3Si2C2 filler via electric current field-assisted sintering technique. Issue 15 (December 2022) - Zhou, Xiaobing; Yu, Teng; Xu, Jie; Li, Yang; Huang, Zhengren; Huang, Qing
Abstract: A novel layered structure material, Pr3 Si2 C2, was synthesized at a low temperature of 850 °C using a molten salt approach for the first time, and subsequently used as the joining filler for carbon fibers reinforced SiC composites (Cf /SiC). A robust near-seamless Cf /SiC joint was successfully obtained at 1509 °C (Ti ) for 30 s, while an ultrafast heating rate of 6000 °C/min was applied via electric field-assisted sintering technology. The near-seamless joining process was attributed to the newly precipitated SiC grains, which were densified well with the Cf /SiC matrix by liquid-assisted sintering. The liquid phase was in-situ formed by the eutectic reaction between Pr3 Si2 C2 and SiC. The shear strength of the near-seamless joint obtained at 1509 °C for 30 s was 17.6 ± 3.0 MPa. The failure occurred in the Cf /SiC matrix. The formation of near-seamless Cf /SiC joints dismisses the issues related to thermal mismatch between Cf /SiC matrices and traditional joining fillers.